Comparison of Different Timing of Multivessel Intervention During Index-Hospitalization for Patients With Acute Myocardial Infarction - Liu, En-Shao; Hung, Cheng Chung; Chiang, Cheng-Hung; Chang, Chia-His; Cheng, Chin-Chang; Kuo, Feng-You; Mar, Guang-Yuan; Huang, Wei-Chun (Frontiers in Cardiovascular Medicine, 2021)
Background: Many patients presenting with acute myocardial infarction (AMI) were found to have a multivessel disease. Uncertainty still exists in the optimal revascularization strategy in AMI patients. The purpose of this study was to assess the outcome of immediate multivessel revascularization compared with staged multivessel percutaneous coronary intervention (PCI) in patients with AMI. Method: This was a nationwide cohort study of 186,112 patients first diagnosed with AMI, 78,699 of whom received PCI for revascularization. Patients who received repetitive PCI during the index hospitalization were referred to as staged multivessel PCI. Immediate multivessel PCI was defined as patients with two-vessel PCI or three-vessel PCI during the index procedure. Cox proportional hazards regression models were performed to evaluate the different indicators of mortality risks in AMI. Result: Immediate multivessel PCI was associated with a worse long-term outcome than staged multivessel PCI during the index admission (log-rank P-value < 0.001). There was a higher incidence of stroke in patients with multivessel PCI during hospitalization. In Cox analysis, immediate multivessel PCI was an independent risk factor for mortality compared to those with staged multivessel PCI, regardless of the type of myocardial infarction. Conclusion: This study demonstrated that performing immediate multivessel PCI for AMI may lead to worse long-term survival than staged multivessel PCI. Our findings emphasized the importance of PCI timing for non-infarct-related artery stenosis and provided information to supplement current evidence.